Logical Environment and Supervisory Regulatory Frameworks for Effective Information Management of Public Universities in Nigeria - Friday Ekahe Abanyam; Janet Achikere Onimawo; Fabian Ugbe Udida; Anthonia Ngozi Ibelegbu; Judith Kanu (Golden Ratio of Data in Summary, 2023)
The study determined the logical environment and supervisory regulatory frameworks for effective information management of public universities in Nigeria. The study adopted descriptive survey research design. The population was 1580 Management staff. 432 respondents were proportionally sampled from each of the Public universities studied. The instrument for data collection was a structured questionnaire developed by the researcher. The questionnaire was face-validated by five experts. The reliability of the instrument was tested using Cronbach Alpha method and yielded an overall coefficient of 0.93. Mean and Analysis of Variance were used to analyze data collected. The findings showed that the management staff agreed to the 42 items measuring the logical environment and Supervisory regulatory actions for effective information management. The findings further showed that no significant difference existed among the opinions of the respondents on the level at which they adopted the logical environment security and supervisory regulatory actions for effective information management of their institutions. It was recommended among others, that the management of Public universities in Nigeria should enact and implement effective policies and laws that support the adoption of information regulatory actions.